2021
DOI: 10.1038/s41598-021-88459-2
|View full text |Cite
|
Sign up to set email alerts
|

Blue light blind-spot stimulation upregulates b-wave and pattern ERG activity in myopes

Abstract: Upregulation of retinal dopaminergic activity may be a target treatment for myopia progression. This study aimed to explore the viability of inducing changes in retinal electrical activity with short-wavelength light targeting melanopsin-expressing retinal ganglion cells (ipRGCs) passing through the optic nerve head. Fifteen healthy non-myopic or myopic young adults were recruited and underwent stimulation with blue light using a virtual reality headset device. Amplitudes and implicit times from photopic 3.0 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 59 publications
(31 reference statements)
2
26
0
Order By: Relevance
“…In the study by Aleman et al, 33 the eye was not exposed to the ON-pathway overstimulating text during OCT imaging, but was presumably exposed to the luminous blue fixation target of the OCT device. Previous studies suggest that brief stimulation (approximately 1 minute) of the melanopsin-driven retinal pathway with blue light upregulates the ON-pathway–mediated response from the dopaminergic retinal amacrine cells, 50 and increases the vitreal dopamine levels. 51 Therefore, we hypothesize that the exposure of the eye to the blue fixation light in the study by Aleman et al 33 might have altered the ON-pathway signaling or triggered other short wavelength–sensitive retinal signaling pathways, 50 , 52 resulting in the observed thickening of the choroid.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Aleman et al, 33 the eye was not exposed to the ON-pathway overstimulating text during OCT imaging, but was presumably exposed to the luminous blue fixation target of the OCT device. Previous studies suggest that brief stimulation (approximately 1 minute) of the melanopsin-driven retinal pathway with blue light upregulates the ON-pathway–mediated response from the dopaminergic retinal amacrine cells, 50 and increases the vitreal dopamine levels. 51 Therefore, we hypothesize that the exposure of the eye to the blue fixation light in the study by Aleman et al 33 might have altered the ON-pathway signaling or triggered other short wavelength–sensitive retinal signaling pathways, 50 , 52 resulting in the observed thickening of the choroid.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study stimulating the blind-spots in myopic eyes with blue-light was reported ( 59 ). Fifteen healthy non-myopic and myopic young adults underwent stimulation with blue light using virtual reality (VR) headset devices.…”
Section: Factors Involved In Myopia Digital Therapeuticsmentioning
confidence: 99%
“…Recently, we have reported significant changes in the ERG and pattern ERG (PERG) responses following stimulation of the blind spot with short-wavelength light 45 . Both the ERG b-wave and PERG P50-N95 amplitudes were significantly increased 20 min after blind spot stimulation, relative to 10 min post-stimulation and baseline.…”
Section: Introductionmentioning
confidence: 99%
“…This effect was found selectively in myopic eyes, which showed significantly greater changes compared to non-myopic eyes. It was hypothesized that this finding might be associated with an increase in DAC activity via retrograde feedback from intrinsically photosensitive retinal ganglion cells (ipRGCs) 45 . It has previously been shown that melanopsin-containing axons of ipRGCs at the optic nerve head respond to stimulation with blue light matching the peak sensitivity of melanopsin 46 .…”
Section: Introductionmentioning
confidence: 99%